Keterampilan Berkewarganegaraan (Civic Skills) Santri pada Pondok Pesantren Salafiyah Nurul Jannah Banjarmasin - Nida Khulfiya; Zainul Akhyar; Muhammad Elmy (Pendidikan IPS FKIP ULM, 2022)
The purpose of this study is to describe the understanding of Nurul Jannah Banjarmasin Islamic Boarding School students about Civic Skills in the social field and describe the understanding of Nurul Jannah Islamic Boarding School students in Civic Skills in the laws. This study used qualitative. To obtain the samples, this study used purposive sampling technique. The use of purposive sampling technique in this study aimed to be able to find out how civic skills in the social and legal fields at the Salafiyah Nurul Jannah Islamic Boarding School in Banjarmasin. The results of this study indicated that the most prominent attitude of them is their politeness and manners and their morals are the main key to being educated by the ustadz/ustadzah there. In addition, the application of the law has been carried out and obeyed by the students. They knew the sanctions that are applied there. So, from there they learn to become law-abiding citizens both within the boarding school and outside the boarding school.Keywords: Civic skills, islamic boarding school, student